1999
DOI: 10.1182/blood.v94.2.434.414k42_434_441
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Depletion Plus Salvage Immunotherapy With Donor Leukocyte Infusions as a Strategy to Treat Chronic-Phase Chronic Myelogenous Leukemia Patients Undergoing HLA-Identical Sibling Marrow Transplantation

Abstract: T-cell depletion (TCD) of the donor marrow graft has been shown to reduce the severity of graft-versus-host disease (GVHD) in patients with chronic-phase (CP) chronic myelogenous leukemia (CML) undergoing HLA-identical sibling allogeneic marrow transplantation. However, there has been a corresponding reduction in the graft-versus-leukemia effect so that any decrease in GVHD-related mortality has been offset by an increased rate of disease relapse. Therapy of recurrent disease with donor leukocyte infusions (DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…We recently reported a low relapse rate in high risk AML patients in remission or good partial remission receiving T cell depleted PBSC grafts after intensified conditioning with radioimmunotherapy(Bunjes, 2002), and some of these patients are included in the present study. Preemptive and prophylactic DLI are highly effective in patients with CML and MM receiving TCD stem cell grafts (Lokhorst et al , 1997; Drobyski et al , 1999; Alyea et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported a low relapse rate in high risk AML patients in remission or good partial remission receiving T cell depleted PBSC grafts after intensified conditioning with radioimmunotherapy(Bunjes, 2002), and some of these patients are included in the present study. Preemptive and prophylactic DLI are highly effective in patients with CML and MM receiving TCD stem cell grafts (Lokhorst et al , 1997; Drobyski et al , 1999; Alyea et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…[580][581][582][583][584][585] In the early studies some of the donor cell infusions caused an appreciable incidence of GVHD, which was sometimes severe or even fatal, and marrow aplasia was also reported. [586][587][588] More recently, improved results have been obtained with (CD8+-depleted) CD4+ donor lymphocyte infusions (CD4+ DLI), which may act by inducing host-reactive cytolytic CD8+ donor T cells to directly or indirectly inhibit the Ph+ progenitors or stem cells. 589,590 The survival of patients who lack HLA-matched siblings and who receive transplants from unrelated HLA-matched donors identified by bone marrow registries is generally substantially lower than recipients of related donor transplants, 591,592 although certain immunologically distinct HLA subtypes fare better than others.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%
“…While T cell‐depleted marrow transplants lower the incidence of acute and chronic GVHD, they increase the risk of leukaemia relapse, graft failure and prolonged immunosuppression (Apperley et al , 1986; Butturini & Gale, 1988; Horowitz et al , 1990; Marmont et al , 1991); there are little data on the performance of T cell‐depleted PBSCT. In an attempt to reduce the risk of GVHD from T‐cell depletion, while conserving useful donor immune function, we and colleagues have performed T cell‐depleted transplantation followed by delayed add‐back of donor T cells (Slavin et al , 1996; Barrett et al , 1998; Drobyski et al , 1999). Using cyclosporine prophylaxis, we showed that the risk of acute GVHD from donor lymphocyte infusions (DLI) was low following substantial T‐cell doses given 45 d or more after marrow transplant (Barrett et al , 1998).…”
mentioning
confidence: 99%